Legal Juridical Analysis of the Responsibility of Village-Owned Enterprises (BUMDes) in Business Activities: A Comparative Review of Indonesian and Malaysian Law - Suratno Pradotodiningrat; Noor Hasnah Binti Hasan (Eastasouth Institute, 2026)
In practice, the implementation of Village-Owned Enterprises (BUMDes) in Indonesia still faces fundamental problems, including weak managerial professionalism, limited administrative capacity, and an underdeveloped legal and financial accountability system. In addition, BUMDes remains highly dependent on village government structures, indicating that it has not yet fully functioned as an independent and professional business entity. Normatively, BUMDes is expected to operate as an autonomous village enterprise with legal certainty, professionalism, and strong accountability in all business activities, including clear liability arrangements in cases of losses or business disputes. However, a significant gap exists in practice, particularly regarding the unclear legal status of BUMDes as an independent legal subject, which creates uncertainty in the allocation of liability between the village government, management, and BUMDes itself. This research aims to analyze the legal regulation of the position and responsibility of BUMDes in Indonesia and Malaysia, as well as the legal mechanisms for liability in cases of loss or disputes, in order to develop a model for strengthening legal certainty in village-based enterprises. The study employs a normative juridical method with a qualitative comparative approach between Indonesian and Malaysian legal concepts. The findings indicate that although BUMDes under Government Regulation No. 11/2021 is formally recognized as a legal entity with economic, social, administrative, and legal responsibilities, its implementation is still constrained by governance weaknesses and unclear liability boundaries. This results in liability ambiguity, requiring stronger structural, substantive, and cultural legal reforms to ensure legal certainty and good governance.